Procalcitonin Predicts Real-Time PCR Results in Blood Samples from Patients with Suspected Sepsis - Mencacci, Antonella (Public Library of Science, 2012)
BACKGROUND: Early diagnosis and rapid bacterial identification are of primary importance for outcome of septic patients. SeptiFast® (SF) real-time PCR assay is of potential utility in the etiological diagnosis of sepsis, but it cannot replace blood culture (BC) for routine use in clinical laboratory. Procalcitonin (PCT) is a marker of sepsis and can predict bacteremia in septic patients. The aim of the present study was to investigate whether PCT serum levels could predict SF results, and could help screening febrile patients in which a SF assay can improve the etiological diagnosis of sepsis. METHODS: From 1009 febrile patients with suspected sepsis, 1009 samples for BC, SF real-time PCR, and PCT determination were obtained simultaneously, and results were compared and statistically analysed. Receiver operating characteristic (ROC) curves were generated to determine the area under the curve and to identify which cut-off of PCT value produced the best sensitivity to detect SF results. RESULTS: Mean PCT values of sera drawn simultaneously with samples SF positive (35.42±61.03 ng/ml) or BC positive (23.14±51.56 ng/ml) for a pathogen were statistically higher than those drawn simultaneously with SF negative (0.84±1.67 ng/ml) or BC negative (2.79±16.64 ng/ml) samples (p<0.0001). For SF, ROC analysis showed an area under the curve of 0.927 (95% confidence interval: 0.899–0.955, p<0.0001). The PCT cut-off value of 0.37 ng/ml showed a negative predictive value of 99%, reducing the number of SF assays of 53.9%, still identifying the 96.4% of the pathogens. CONCLUSION: PCT can be used in febrile patients with suspected sepsis to predict SF positive or negative results. A cut-off value of 0.37 ng/ml can be considered for optimal sensitivity, so that, in the routine laboratory activity, SF assay should not be used for diagnosis of sepsis in an unselected patient population with a PCT value <0.37 ng/ml.